Omics-based identification of an NRF2-related auranofin resistance signature in cancer: Insights into drug repurposing. (January 2023) - Falchetti, Marcelo; Delgobo, Marina; Zancanaro, Helena; Almeida, Karoline; das Neves, Raquel Nascimento; dos Santos, Barbara; Stefanes, Natália Marcéli; Bishop, Alexander; Santos-Silva, Maria Cláudia; Zanotto-Filho, Alfeu
Abstract: Auranofin is a thioredoxin reductase-1 inhibitor originally approved for the treatment of rheumatoid arthritis. Recently, auranofin has been repurposed as an anticancer drug, with pharmacological activity reported in multiple cancer types. In this study, we characterized transcriptional and genetic alterations associated with auranofin response in cancer. By integrating data from an auranofin cytotoxicity screen with transcriptome profiling of lung cancer cell lines, we identified an auranofin resistance signature comprising 29 genes, most of which are classical targets of the transcription factor NRF2, such as genes involved in glutathione metabolism ( GCLC, GSR, SLC7A11 ) and thioredoxin system ( TXN, TXNRD1 ). Pan-cancer analysis revealed that mutations in NRF2 pathway genes, namely KEAP1 and NFE2L2, are strongly associated with overexpression of the auranofin resistance gene set. By clustering cancer types based on auranofin resistance signature expression, hepatocellular carcinoma, and a subset of non-small cell lung cancer, head-neck squamous cell carcinoma, and esophageal cancer carrying NFE2L2 / KEAP1 mutations were predicted resistant, whereas leukemia, lymphoma, and multiple myeloma were predicted sensitive to auranofin. Cell viability assays in a panel of 20 cancer cell lines confirmed the augmented sensitivity of hematological cancers to auranofin; an effect associated with dependence upon glutathione and decreased expression of NRF2 target genes involved in GSH synthesis and recycling ( GCLC, GCLM and GSR ) in these cancer types. In summary, the omics-based identification of sensitive/resistant cancers and genetic alterations associated with these phenotypes may guide an appropriate repurposing of auranofin in cancer therapy. Graphical abstract: Image 1 Highlights: A 29-gene auranofin resistance signature was obtained from lung cancer datasets. Auranofin signature is enriched with classical NRF2 target genes. KEAP1/NRF2 mutations are key features associated with signature upregulation. Hematological cancers express low levels of auranofin resistance gene set. Hematological cancers are more sensitive to auranofin than solid cancer cell lines.